2014
DOI: 10.1111/febs.13083
|View full text |Cite
|
Sign up to set email alerts
|

Role of PRC2‐associated factors in stem cells and disease

Abstract: The Polycomb group (PcG) of proteins form chromatin‐binding complexes with histone‐modifying activity. The two main PcG repressive complexes studied (PRC1 and PRC2) are generally associated with chromatin in its repressed state. PRC2 is responsible for methylation of histone H3 at lysine 27 (H3K27me3), an epigenetic mark that is linked with numerous biological processes, including development, adult homeostasis and cancer. The core canonical complex PRC2, which contains the EZH1/2, SUZ12 and EED proteins, may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 94 publications
1
72
0
2
Order By: Relevance
“…The PRC2 complex architecture is not as heterogeneous as the PRC1 complex (Fig. 2), yet several cofactors have recently been identified that associate it with PRC2 members in ESCs (92). In the past years, the Jumanji protein Jarid2 was identified as the first protein to interact directly, via its interaction with Suz12, with the core PRC2 complex in ESCs.…”
Section: Do These Complexes Have Redundant Functions In Escs?mentioning
confidence: 99%
“…The PRC2 complex architecture is not as heterogeneous as the PRC1 complex (Fig. 2), yet several cofactors have recently been identified that associate it with PRC2 members in ESCs (92). In the past years, the Jumanji protein Jarid2 was identified as the first protein to interact directly, via its interaction with Suz12, with the core PRC2 complex in ESCs.…”
Section: Do These Complexes Have Redundant Functions In Escs?mentioning
confidence: 99%
“…Several lines of evidence suggest that EZH2 deregulation is an important driver of cancer development and progression and that inactivation of EZH2 may be therapeutically effective in many cancers [4,5,11,12,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89] . EZH2 is highly expressed in a wide range of cancer types, including lung, breast, colon, prostate, bladder and pancreatic cancer, as well as sarcomas and lymphomas [4,5,11,12,76,77,80,82,83,[85][86][87][88] . Correspondingly, overexpression of EZH2 often correlates with advanced stages of human cancer progression and poor prognosis [4,12,76] .…”
Section: Prc2 and Diseasesmentioning
confidence: 99%
“…Cette étude (NCT01897571) initiée en 2013, devrait se terminer en 2020. Cependant, des résultats préliminaires montrent qu'une réponse partielle ou totale a pu être observée chez 9 des 15 patients atteints de lymphomes non-hodgkiniens 5 . Les molécules GSK126 et EI1 sont actives à la fois sur les deux formes d'EZH2.…”
Section: Rôle Suppresseur De Tumeur D'ezh2unclassified
“…Elles augmentent son activité catalytique ou modifient son adressage et sa liaison à la chromatine. C'est, par exemple, le cas du facteur chromatinien JARID2 (Jumonji and ATrich interaction domain containing 2) capable de se lier à l'ADN et d'induire l'adressage du complexe PRC2 à la chromatine [5]. Les protéines du groupe Polycomb (PcG) sont des facteurs épigénétiques qui ont été initialement décou-verts chez la drosophile pour leur implication dans la répression des gènes Hox au cours du développement 1 .…”
unclassified